The structure and content of the general psychological training of elite Paralympic athletes - Banayan, A. A.; Vorobev, S. A.; Kiseleva, E. A.; Kryuchkov, A. S. (Theory and Practice of Physical Culture, 2021)
The aim of the article is to reveal the features of the structure and content of general psychological training in Paralympic sports at various stages considernosologies. Research results and conclusions. The methodological foundations, modern approaches and concepts for effective planning, organization and implementation of general psychological training in elite Paralympic sports have been determined. The necessity of paying respect to the international Paralympic sports classification was revealed, in accordance with which athletes belong to different sports classes (functional), which determine the specificity of the organization and conduct the psychological training of high-class Paralympic athletes. The features of the structure and content of the general psychological training of Paralympians at the stages of sports specialization and elitehave been revealed.